Endoscopic negative pressure therapy for duodenal leaks - Wichmann, Dörte; Stüker, Dietmar; Schweizer, Ulrich; Senne, Moritz; Duckworth-Mothes, Benedikt; Zerabruck, Emanuel; Königsrainer, Alfred; Bachmann, Jeannine (Frontiers in Surgery, 2023)
Background and study aim: Endoscopic negative pressure therapy (ENPT) is well established in the treatment of perforations of various etiologies in the upper and lower gastrointestinal tract. For duodenal perforations exist only case reports and series. Different indications are possible for ENPT in duodenal position: primary therapy for leaks, preemptive therapy after surgery for example, after ulcer suturing or resection with anastomoses, or as second line therapy in cases of recurrent anastomotic insufficiencies with leakage of duodenal secretion. Methods: A retrospective 4-year case series of negative pressure therapy in duodenal position indicated by different etiologies and a comprehensive review of current literature on endoscopic negative pressure duodenal therapy are presented. Results: Patients with primary duodenal leaks n=6 and with duodenal stump insufficiencies n=4 were included. In seven patients ENPT was the first line and sole therapy. Primary surgery for duodenal leak was performed in n=3 patients. Mean duration of ENPT was 11.0 days, mean hospital stay was 30.0 days. Re-operation after start of ENPT was necessary in two patients with duodenal stump insufficiencies. Surgery after termination of the ENPT was not necessary in any patient. Discussion: In our case series and in the literature, ENPT has been shown to be very successful in the therapy of duodenal leaks. A challenge in ENPT for duodenal leaks is the appropriate length of the probe to safely reach the leak and keep the open pore element at the end of the probe in place despite intestinal motility.